RATIONALITY AND ETHICS IN ORGANIZATIONS - Giraldo Garcés, Gregorio (Cuadernos de Administración, 2007)
The organizations in the contemporary present a variety of characteristics that shape its reason for being. Showing to society as an actor in the game of intersubjective relations proper of the system in which it lives. In contemporary ethics and morality appear in the organizations dynamics in a postmodern way, that is, the ideal of modern ethics and morality that designated right and wrong, no longer are categorical imperatives that guide the actions of these. The conceptual Support of tbis reflection is in the ideas of Lipovetsky (2000), who introduced a marriage between ethics and business where ethics has a new role due to the development of business. Tbus, the proposal shows the relationship between rationality, ethics and business logic, with the interest of developing a critical reflection about the reason for being of the contemporary organizations and their social responsibility.